2019
DOI: 10.1177/2471549219830284
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Comorbidities and Postoperative Complications Do Not Influence Patient-Reported Satisfaction Following Humeral Head Resurfacing: Mid- to Long-term Follow-up of 106 Patients

Abstract: Background: Humeral head resurfacing (HHR) has emerged as an alternative treatment for glenohumeral osteoarthritis. We investigated the outcomes of HHR using validated patient-reported outcome (PRO) measures. Methods: A retrospective review was performed on 213 patients who underwent HHR. A PRO follow-up was performed by administering a questionnaire including the American Shoulder and Elbow Society (ASES) score, Brophy activity survey, short form of the Disabilities of the Arm, Shoulder and Hand (quickDASH) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Comparatively, Werner et al 12 found that of the 38 shoulders that underwent humeral head resurfacing at their institution, the mean Constant score improved to 55.4 AE 23.6 points, although symptomatic glenoid erosion resulted in revision in 37% of patients. Beck et al 13 found that preoperative comorbidities and postoperative complications did not impact overall patient satisfaction or most patient-reported outcome measures at a mean follow up of 5.6 years postoperatively, indicating the clinical viability of humeral resurfacing on a wide array of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, Werner et al 12 found that of the 38 shoulders that underwent humeral head resurfacing at their institution, the mean Constant score improved to 55.4 AE 23.6 points, although symptomatic glenoid erosion resulted in revision in 37% of patients. Beck et al 13 found that preoperative comorbidities and postoperative complications did not impact overall patient satisfaction or most patient-reported outcome measures at a mean follow up of 5.6 years postoperatively, indicating the clinical viability of humeral resurfacing on a wide array of patients.…”
Section: Discussionmentioning
confidence: 99%